1988
DOI: 10.1172/jci113317
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis type I subtypes. Presence of immunologically cross-reactive material and in vitro enhancement of the residual alpha-L-iduronidase activities.

Abstract: The enzymatic and immunologic properties of the defective residual a-L-iduronidase activities were investigated in fibroblast extracts from the three subtypes of mucopolysaccharidosis type I, Hurler (MPS IH), Scheie (MPS IS), and HurlerScheie (MPS IH-S) diseases. Using 4-methylumbelliferyl-a-L-iduronide (4MU-a-Id), the activities in fibroblast extracts from all three subtypes were less than 0.1% of normal. Rocket immunoelectrophoresis with monospecific rabbit anti-human a-L-iduronidase polyclonal antibodies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Previously, we reported that the catalytic activities of two other lysosomal hydrolases which also de grade GAGs, a-L-iduronidase [23] and arylsulfatase B [24], also were enhanced by these effector molecules. These data suggest that the active sites of some lysosomal hydrolases may be maintained by the presence of essen tial sulfhydryl groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the catalytic activities of two other lysosomal hydrolases which also de grade GAGs, a-L-iduronidase [23] and arylsulfatase B [24], also were enhanced by these effector molecules. These data suggest that the active sites of some lysosomal hydrolases may be maintained by the presence of essen tial sulfhydryl groups.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with all forms of MPS I have unmeasurable endogenous α- l -iduronidase activity though those with attenuated disease may synthesize trace amounts of endogenous enzyme depending on the underlying genetic mutation (1,25). This cross-reactive immunologic material (CRIM) is recognized as self protein by the host immune system and its presence is thought to mitigate development of serum antibodies to intravenous recombinant human enzyme in CRIM-positive as compared to CRIM-negative subjects (18).…”
Section: Discussionmentioning
confidence: 99%
“…Since each subtype of MPS accumulates one or more particular types of GAGs, the chemical composition of these undegraded moieties most likely plays a role in causing specific disease manifestations. Disease severity may increase with the number of different accumulating GAG types; however, it is interesting to note that with MPS I, there are subtypes that are defined by varying disease severity [24, 25], indicating that there are factors beyond GAG type and level of accumulation that impact pathology.…”
Section: Pathophysiology Of Spine Disease In Mpsmentioning
confidence: 99%